Traumatised women and men in discourse with Orpah as role model - Stassen, Stefan (Old Testament essays, 2007)
In narrative therapy, as invented and developed by Michael White and David Epston, people are encouraged to challenge the stories that are told to - and about - them by the 'empowered' society. Less empowered people in society are led to believe a lot of lies about themselves, told by the controlling and dominating part of society. We call those lies 'grand narratives'. The grand narrative should be challenged and replaced by a more balanced and complete version of people's lives. The Ruth narrative could help a lot with such a process. We could describe it as 'pastoral storytelling' (Eugene Peterson), whereby people get the chance to identify with certain roleplayers in - or outside - the narrative and thus be stimulated to rewrite their own narratives. In this study the readers' responses of two groups of traumatised women are compared to the responses of two groups of traumatised men. How do these different types of people react to the Ruth narrative, and what help do they get from this narrative to challenge the grand narratives enforced on them by the dominant society? There are several possible perspectives from which the book can be read, as well as different angles from the viewpoint of the characters in the story. These are all used as pointers according to which the reader can respond to the text of Ruth.